The Tabula Lugdunensis a critical edition with translation and commentary - Claudius Kaiser des Römischen Reiches v10-54 (Cambridge University Press, 2020)
Unearthed in 1528 at Lyon, the Tabula Lugdunensis preserves the longest speech of a Roman emperor to survive in epigraphic form. In AD 48 Claudius addressed the senate to press a petition by elites of north-western Gaul to hold senatorial rank and office. In support he demonstrated Rome's history of constitutional innovation, particularly in integrating outsiders, and asserted a commitment to recruiting worthy provincial senators such as he claims the Gauls to be. The speech offers important evidence for the history and rhetoric of Roman political integration, unparalleled Etruscan testimony about Regal Rome, and insight into the Latin language and oratory of the early Principate. Uniquely, the Tabula can be set beside Tacitus' version of Claudius' speech in Annals 11 to provide a case-study of ancient historiographical practice. This edition contains a newly-edited text of the Tabula, an English translation, and a comprehensive introduction and commentary